Strategi Mempertahankan Program TV Segmen Anak-anak pada Televisi FTA (Free To Air) - Damayanti, Ratih Damayanti; Ciptono Setyobudi; Zulia Kusuma Rahayu (Airlangga University, 2025)
ABSTRACT Children in Indonesia watch online videos with parental supervision. Streaming video services, such as YouTube, Netflix, and others have eclipsed the position of television. The existence of YouTube Kids, which provides safety features and content curation, is the main choice for parents to become a media for watching children's shows for their children. With that, this study aims to explore the strategies used by Free To Air (FTA) television stations, namely Mentari TV in facing competition with streaming video services. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation studies. The results of this study show that Mentari TV airs children's programs, such as Baby Bus, Tayo, Keluarga Somat, Pororo, and Pokemon. Each program provides life lessons with educational, entertainment, and moral values. In facing competition with video streaming services, Mentari TV relies on a strategy of re-running programs and also airing based on time segmentation. In addition, a thematic umbrella program is also used to increase audience engagement through a collection of flagship programs and is useful for ensuring viewing quality. Keywords: FTA Television; Mentari TV; Re-running; Thematic Umrella; Streaming Video.